ANALISIS FAKTOR-FAKTOR PENYEBAB TINGKAT KREDIT MACET DI KOPERASI MANTOARI DAIT PONTIANAK - Celvin, Agustinus Figa; Warneri, Warneri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The aim of this research is to determine the factors causing the level of bad credit in the Mantoari Dait Pontianak cooperative. The approach used is descriptive qualitative. Observations and interviews were carried out on 3 employees of the Mantoari Dait cooperative in various fields and 3 customers with a total of 6 informants. Data collection was carried out by observation and in-depth interviews as well as several documentation relevant to the research. The results of this research found that the factors causing the level of bad credit are internal factors and external factors. There are 2 ways to overcome bad credit at the Mantoari Dait Pontianak cooperative, namely efforts to resolve bad credit carried out by the cooperative, namely trying to contact customers who experience credit jams, and coming directly to be able to find solutions together in an effort to overcome credit jams experienced by cooperative members and provide understanding. about how to manage finances by setting aside a portion of the results of work that are channeled to pay loan installments in cooperatives. Negotiate to resolve obligations voluntarily with customers, by reducing interest or paying the principal due on credit loans. Take firm action by confiscating or taking collateral promised as collateral when making a loan. The second effort is to resolve credit congestion caused by customers. Customers can make realistic payment plans based on their financial ability to pay their credit installments.